2011
DOI: 10.1002/jsfa.4232
|View full text |Cite
|
Sign up to set email alerts
|

Sensorically and antimicrobially active metabolite production of Lactobacillus strains on Jerusalem artichoke juice

Abstract: Our results showed that lactobacilli can be used for the fermentation of Jerusalem artichoke, which in this form could be used, alone or mixed with other raw food material, as a new synbiotic functional food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 73 publications
0
19
0
Order By: Relevance
“…Similarly, increased Firmicute abundance might enhance the energy absorption of piglets fed with EOs in this study. Lactobacillales within Bacilli are recognized beneficial bacteria, which helps maintain normal intestinal function and promote the health of body (Zalán et al, 2011). Streptococcaceae and Streptococcus were found to be negatively associated with inflammation in previous studies (Ferná ndez et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, increased Firmicute abundance might enhance the energy absorption of piglets fed with EOs in this study. Lactobacillales within Bacilli are recognized beneficial bacteria, which helps maintain normal intestinal function and promote the health of body (Zalán et al, 2011). Streptococcaceae and Streptococcus were found to be negatively associated with inflammation in previous studies (Ferná ndez et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This was achieved by medium supplementation with Mn +2 , which is an essential growth factor for lactic acid bacteria. Metabolites developed during fermentation of Jerusalem artichoke juice with different Lactobacillus strains (L. plantarum, L. paracasei, L. casei, L. rhamnosus and L. curvatus) were analyzed by Zalán et al (2011). They found only three organic acids produced by the tested strains: lactic, acetic and succinic acid.…”
Section: Organic Acids Production During Fermentationsmentioning
confidence: 99%
“…Zalán et al . () showed that all strains of tested lactic acid bacteria grew well to approximately 10 9 cfu/mL in JA juice. In addition, adding JA concentrate to milk and oat hydrolysate resulted in substantial stimulation of various probiotic dairy starter cultures in yoghurt‐like products (Semjonovs et al .…”
Section: Introductionmentioning
confidence: 90%